Language and power - Watzke, John L.; Miller, Paul Chamness; Mantero, Miguel (Readings in language studies, 2022)
The International Society for Language Studies (ISLS) introduces its second volume in the series Readings in Language Studies with Language and Power, a text that represents international perspectives on power and bilingualism, identity in professions, media, the learner, and pedagogy. Founded in 2002, ISLS is a world-wide organization of volunteers, scholars and practitioners committed to critical, interdisciplinary, and emergent approaches to language studies.